Effect of iron treatment on nutritional status of children with iron deficiency anemia - Leon Agustian; Tiangsa Sembiring; Ani Ariani; Bidasari Lubis (Indonesian Pediatric Society, 2009)
Background Iron has been shown to improve growth in childrenwith iron deficiency anemia (IDA), as indicted by increases inheight and weight. Frequently, malnutrition and iron deficiencycoexist.Objective To determine the effect of iron treatment on nutritionalstatus in children with IDA.Methods A randomized placebo-controlled clinical trial wasconducted at Bilah Hulu, a subdistrict of Labuhan Batu, NorthSumatera, Indonesia, between November 2006 and February2007. Iron deficiency anemia was diagnosed if there anemiawas present along with MCHC <31%, RDW index >220 andMentzer index> 13. Elementary school children (8-12 years old)with IDA were randomly assigned to either receive a daily therapyof 6 mg iron/kg/day or a placebo for three months. Nutritionalstatus was evaluated by anthropometric assessment before andafter intervention.Results From 300 subjects recruited, there were 111 (3 7 .2%)with iron deficiency anemia; 108 of them completed the therapy.After intervention, the iron and placebo groups had differentmean hemoglobin concentrations (P <0.05), but there was nosignificant difference in mean weight and height gain betweenthe two groups.Conclusion A significant increase in hemoglobin concentrationwas seen when iron was given, but did not affect weight and height increase in the subjects.